Chinese herbal medicine for migraine management: A hospital-based retrospective analysis of electronic medical records - Lyu, Shaohua; Zhang, Claire Shuiqing; Sun, Jingbo; Weng, Heng; Xue, Charlie Changli; Guo, Xinfeng; Zhang, Anthony Lin (Frontiers in Medicine, 2022)
Background: Migraine is a chronic neurological disease causing significant socioeconomic burden and impaired quality of life. Chinese medicine is commonly used for migraine in China. Clinical trials have generated evidence of the effectiveness of Chinese medicine therapies for migraine. However, little is known about how to use these therapies to treat migraine in real-world clinical settings. Method: In this retrospective study, we analyzed data from the electronic medical records of 2,023 migraine patients who attended the Guangdong Provincial Hospital of Chinese Medicine between July 2018 and July 2020. Results: More than three-quarters (77.21%) of the patients were female. Most (78.20%) of the patients were aged between 18 and 50 years, 18.49% were aged above 50 and the remaining 3.31% were under 18. Sleep disorders were the most documented comorbidity, occurring in 27.29% of patients, and more common in females (29.77%) than male (18.87%). Fatigue was the most frequently reported trigger of migraine attacks among all patients (9.39%), while menstruation was the most common trigger for female patients (10.24%). Less than a quarter of patients (21.01%) reported a history of taking analgesic medication for their migraine. The median treatment duration reported by the patients was 10 days. Chinese herbal medicine (CHM) was the predominant treatment for migraine at the hospital (88.48%), while pharmacotherapies were prescribed to 28.97% of the patients. CHM was prescribed more often as a sole treatment (53.58% of patients) than combined with pharmacotherapies (27.39% of patients). Among patients who reported improvements after taking CHM, the most frequently used herbs were fu ling and chuan xiong. The most frequent patented CHM product was tong tian oral solution, and the main herbal formulae were chuan xiong cha tiao san and yi qi cong ming tang. Conclusion: CHM formulae such as chuan xiong cha tiao san and yi qi cong ming tang, patented CHM product tong tian oral solution, and some herbs are potentially effective treatments for migraine. As such, CHM can be used as an alternative to conventional pharmacotherapies for migraine, and worth further evaluation in randomized controlled trials.